KEBERHASILAN KEBIJAKAN PENANGANAN KORUPSI PEMERINTAH REPUBLIK RAKYAT CINA (RRC) SEJAK TAHUN 2002 - , Marissa Devi Alexandra Pontoan, Dr. Siti Muti'ah S., MA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
In The era globalisation today, corruption was in fact became a serious threat for several countries in the world. This is due to an enormous loss grade and caused mentality loss and development equality in the related countries. Corruption was actually also developed in China. Corruption characteristics in China were very different with the other countries, where it was affected by socio- cultural most of histories in the past. This was also caused difficulties to handle corruption in China than in the other countries. Since 2002 handling corruption achievement in China was very successful. This could be even from some main factors namely the index development such as what had issued by TI (Transparency International), Chinese budget amount that was successful to save, and also a lot of corruptors that were being sued to the court. Chinaâs success in handling corruption was in fact related to two things namely: strict and egalitarian law enforcement and bureaucracy simplification. The first policy was related to law enforcement without discrimination whether they were from elite-bureaucrats or ordinary people. Part of them was dead sentenced. This was what caused have a fright-effect so that new corruption cases would not repeated. The next policy was a bureaucracy simplification. The important meaning was as a corruption handling part in China was to cut unnecessary steps, where eventually was positively affected for China economic development and promoted monitoring licence and other bureaucracy forms. Image in China corruption and the two strategies above were about law enforcement and bureaucracy simplification would be discussed in depth in this research.